2016
DOI: 10.18632/oncotarget.9668
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo transducers TAZ/YAP and their target CTGF in male breast cancer

Abstract: Male breast cancer (MBC) is a rare disease and its biology is poorly understood. Deregulated Hippo pathway promotes oncogenic functions in female breast cancer. We herein investigated the expression of the Hippo transducers TAZ/YAP and their target CTGF in MBC. Tissue microarrays containing samples from 255 MBC patients were immunostained for TAZ, YAP and CTGF. One hundred and twenty-nine patients were considered eligible. The Pearson's Chi-squared test of independence was used to test the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…When YAP is dephosphorylated, it is transported to the nucleus where it activates downstream factors. CTGF (connective tissue growth factor), one downstream effector protein of YAP 44, promotes fibroblast proliferation and collagen deposition 45 (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…When YAP is dephosphorylated, it is transported to the nucleus where it activates downstream factors. CTGF (connective tissue growth factor), one downstream effector protein of YAP 44, promotes fibroblast proliferation and collagen deposition 45 (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…Two investigators (ADB and MM) evaluated immunoreactivity. The modalities used for assessing TAZ, YAP, CTGF, hormone receptors and Ki‐67 levels were detailed elsewhere (Shaaban et al, ; Di Benedetto et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…In MBC, we have previously reported that the expression of TAZ/YAP and their established target CTGF conferred inferior survival outcomes (Di Benedetto et al, ). To provide further insights into the oncogenic role of TAZ/YAP in such an uncommon tumor, we herein assessed AXL, a member of the TAM family of receptor tyrosine kinases (RTKs) (Graham et al, ), as the Axl gene is a direct target of the Hippo transcriptional machinery (Azzolin et al, ; Zanconato et al, ).…”
mentioning
confidence: 99%
“…Then, YAP translocates to the nucleus, where it forms a complex with TEAD and regulates the expression of multiple genes [6][7][8]. Numerous studies have shown the up-regulation of YAP in the tumors, such as liver cancer, breast cancer and so on [9][10][11][12]. It has been reported that the expression of TAZ is positively regulated by EBV-LMP1 and contributes to cell proliferation and epithelial-mesenchymal transition in NPC [13].…”
Section: Introductionmentioning
confidence: 99%